Disease hazard identification and assessment associated with wildlife population declines. (May 2015) - Pacioni, Carlo; Eden, Paul; Reiss, Andrea; Ellis, Trevor; Knowles, Graeme; Wayne, Adrian F.
Summary Disease is increasingly being recognised as a risk factor in declining wildlife populations around the globe. However, there are limited protocols to assess disease risks in declining wildlife. Using epidemiological principles, we define a step‐by‐step framework to complete this complex and critical task. As an example, we assessed the potential role of diseases in relation to the decline of the woylie or brush‐tailed bettong (Bettongia penicillata ogilbyi) in Western Australia. Between 1999 and 2006, woylie populations declined by 90%. The wildlife disease risk assessment began with a list of all known or suspected diseases to which the woylie, a species of macropod, is susceptible. This list was assessed against the spatial, temporal and demographic characteristics of the decline. Diseases causing widespread and high mortalities or debilitation leading to predation received high scores. Based on this assessment, priority diseases or pathogens for investigation identified were haemoparasites, gastrointestinal helminths, Neospora caninum, Toxoplasmosis (Toxoplasma gondii), Encephalomyocarditis virus, Macropod Orbiviruses (Wallal virus and Warrego virus), Macropod Herpesviruses (Macropodid herpesvirus 1 and 2) and Salmonella spp.